2020
DOI: 10.1038/s41430-020-00757-6
|View full text |Cite
|
Sign up to set email alerts
|

How the Covid-19 epidemic is challenging our practice in clinical nutrition—feedback from the field

Abstract: The viral epidemic caused by the new Coronavirus SARS-CoV-2 is responsible for the new Coronavirus disease-2019 (Covid-19). Fifteen percent of the Covid-19 patients will require hospital stay, and 10% of them will need urgent respiratory and hemodynamic support in the intensive care unit (ICU). Covid-19 is an infectious disease characterized by inflammatory syndrome, itself leading to reduced food intake and increased muscle catabolism. Therefore Covid-19 patients are at high risk of being malnourished, making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 62 publications
2
78
1
3
Order By: Relevance
“…This study showed that SARS-CoV-2 infection was associated with more severe appetite loss when compared to the control group. This finding may help explain the malnutrition in COVID-19 patients reported in previous studies ( Thibault et al, 2020 , Li et al, 2020 ). Oral hygiene, especially tongue coat, could reduce the sense of taste ( Solemdal et al, 2012 ).…”
Section: Discussionsupporting
confidence: 70%
“…This study showed that SARS-CoV-2 infection was associated with more severe appetite loss when compared to the control group. This finding may help explain the malnutrition in COVID-19 patients reported in previous studies ( Thibault et al, 2020 , Li et al, 2020 ). Oral hygiene, especially tongue coat, could reduce the sense of taste ( Solemdal et al, 2012 ).…”
Section: Discussionsupporting
confidence: 70%
“…First, COVID-19 inflamatory responses lead to reduced food intake of patients. Secondly, it increases the muscle catabolism resulting in patients at high risk of being malnoursihed ( Thibault, Coëffier, et al, 2020 ). Therefore, a implementing a nutritional assessment for all patients with COVID-19 is essential.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 infection is characterized by inflammatory syndrome leading to increased muscle catabolism and increased protein-energy needs. There is a vicious circle, because dyspnea, oxygen therapy and isolation hinder food intake [ 283 ]. In a study involving 403 patients hospitalized for COVID-19, 70% of them left the hospital with malnutrition and an average loss of 6.5 kg [ 284 ].…”
Section: Clinical Presentation Of Covid-19 and Risk Factorsmentioning
confidence: 99%